Manajemen Guru dan Tenaga Kependidikan dalam Perspektif Manajemen Strategik Pendidikan di Sekolah Dasar: Strategi Penguatan Mutu Pendidikan melalui Perencanaan Berbasis Data - Nurhadi, Ahmad Nurhadi; Asep Agus Salim; Elim Halimah Sa’diyah; Rista Maifi; Noni Nurasiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher and educational personnel management plays a strategic role in improving the quality of primary education. However, the management of human resources in schools is often carried out administratively and has not been optimally integrated with data-driven decision-making. This study aims to analyze teacher and educational personnel management from the perspective of educational strategic management and to formulate strategies for strengthening educational quality through Data-Based Planning (Perencanaan Berbasis Data/PBD). This study employed a library research method with a qualitative descriptive approach. Data sources consisted of national and international scientific articles, educational policy documents, and official reports published between 2020 and 2025. Data were collected through documentation techniques and analyzed using content analysis. The findings indicate that strategic management provides a systematic framework for planning, organizing, implementing, and evaluating teacher and educational personnel management. Furthermore, Data-Based Planning supported by Education Report Cards, Dapodik, and educational quality indicators enables schools to make more objective and effective decisions. The study proposes a conceptual model integrating strategic educational management, data-based planning, and teacher management as a strategy to improve the quality of primary education. This integration contributes to strengthening teacher professionalism, improving organizational performance, and supporting sustainable educational quality improvement.Keywords: strategic management, teacher management, educational personnel, data-based planning, primary education